The Role of Stress-related Biomarkers, Immune-inflammatory Pathways, and Genetic Polymorphisms in Cognitive-behavioral Therapies for Chronic Low Back Pain and Depression - Adrián Pérez-Aranda; Carla Rodríguez-Freire; Juan P. Sanabria-Mazo; Albert Feliu-Soler; Mar Grasa; Albert Carrillo; Montserrat Esteve; Oriana Filluelo; Araceli Rosa; Ariadna Colomer-Carbonell; Patricia Mas-Bermejo; Lance M. McCracken; et al. (The Clinical Journal of Pain, 2026)
Objectives: This study aimed to (a) evaluate the effects of Acceptance and Commitment Therapy (ACT) and Behavioral Activation Therapy for Depression (BATD) on immune-inflammatory biomarkers in patients with chronic low back pain and comorbid depression, and (b) explore whether these biomarkers and genetic polymorphisms in BDNF and FKBP5 predict treatment response. Methods: A total of 114 female participants (mean age=57.5 y) were randomized to a group-based therapy delivered via videoconference (ACT or BATD, both added to treatment-as-usual [TAU]) or TAU alone. Serum IL-6, CXCL-8, TNF-α, IL-1β, IL-10, high-sensitivity CRP, cortisol, vitamin D, and hair cortisol and cortisone were assessed at baseline and post-treatment, whereas BDNF and FKBP5 genotypes were assessed at baseline only. Clinical outcomes included pain interference, pain intensity, depressive symptoms, anxiety, stress, and pain catastrophizing. Results: Psychological interventions did not significantly change biomarker levels compared to TAU. However, ACT and BATD led to significant improvements in different clinical variables (e.g., pain interference, depressive symptomatology, anxiety, pain catastrophizing). Baseline biomarkers and FKBP5 genotype predicted treatment response, with some effects specific to ACT or BATD (e.g., cortisol, vitamin D) and others general across groups (e.g., hair cortisol, cortisone, CXCL-8); TNF-α and hs-CRP showed exploratory, descriptive associations with responder status. Discussion: While ACT and BATD improved clinical outcomes, their effects on immune-inflammatory biomarkers were not significant. Nevertheless, specific baseline biomarkers and genetic factors may serve as predictors of treatment response. These findings underscore the need to further explore the interaction between psychological therapies, biological processes, and individual variability in treatment outcomes.